SIDE EFFECTS OF INJECTABLE AND ORAL CONTRACEPTIVE AND UNINTENDED PREGNANCY AMONG REPRODUCTIVE WOMEN IN INDONESIA - Maria Gayatri; Dian Kristiani Irawaty (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2021)
Using contraception is essential for protecting women from the risk of unintended pregnancy. However, contraceptive discontinuation, caused by side effects of contraceptives or health problems, is still high. This study aimed to assess the impact of injectable and pill contraception discontinuation due to side effects or health problems on unintended pregnancy among women aged 15-49 years in Indonesia. This study is based on the 2017 Indonesia Demographic and Health Survey. As many as 1,613 women who discontinued their oral contraceptives and 5,022 women who discontinued their injectables were followed retrospectively. Pregnancy rates were tested for differences between categories using survival analysis. It was found that one year after stopping contraceptives due to side effects, almost 16-17% of oral/injectable contraceptive users were already pregnant. The pregnancy rate was higher among women aged less than 25 years. Unplanned pregnancy occurred more frequently among women who were not working than women who were working. Counseling services need to be strengthened by improving provider knowledge and skills to give comprehensive information including contraceptives’ side effects.